THE EFFECT OF AVERAGE AGE AND LEVEL OF EDUCATION ON PEOPLE'S PURCHASING POWER IN INDONESIA IN 2022 - Zefanya Grace Enos Simbolon; Pardomuan Robinson Sihombing (Sekolah Tinggi Ilmu Ekonomi Graha Kirana, 2025)
Education and age are two demographic factors that are believed to have an influence on individuals' economic conditions, including their purchasing power. Understanding the relationship between these variables is important in designing effective economic policies. The purpose of this study is to see how age and education level impact people's purchasing power in Indonesia. Purchasing power, which can be affected by demographic factors such as age and educational background, is an important indicator of a person's economic well-being. This study employs quantitative techniques using multiple linear regression analysis using cross-sectional data from 34 provinces in Indonesia in 2021. Secondary data sources include the Central Bureau of Statistics (BPS) and other relevant sources. The results showed that, with a coefficient of 0.352, education level has a positive and significant influence on purchasing power. This shows that the higher a person's level of education, the greater their ability to purchase goods and services. On the other hand, the age variable does not have a significant influence on purchasing power, but the productive age group of 25 to 55 years old seems to have better wealth. This result can be used by the government to increase people's purchasing power by making economic policies and programmes to increase access to education.